2021
DOI: 10.3390/antiox10121982
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the 1H-NMR Serum Metabolic Profile of Takotsubo Patients Reveals Systemic Response to Oxidative Stress

Abstract: Takotsubo syndrome (TTS) presents as an acute coronary syndrome characterized by severe left ventricular (LV) dysfunction and non-obstructive coronary artery disease that typically shows spontaneous recovery within days or weeks. The mechanisms behind TTS are mainly related to beta-adrenergic overstimulation and acute endogenous catecholamine surge, both of which could increase oxidative status that may induce further deterioration of cardiac function. Although several studies reported evidence of inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Reduced synthesis of Kreb's cycle intermediates and adenosine triphosphate results from an increase in myocardial glucose intake combined with a decrease in the available glycolysis metabolites, giving rise to a different metabolic profile in TTS than patients with AMI [28]. In a recent study, serum metabolic profile analysis showed that TTS is associated with a substantial rise in the plasmatic concentrations of ketone bodies, 2-hydroxybutyrate, and markers associated with fatty acid metabolism, which leads to endothelial dysfunction through the production of oxygen radicals and vascular inflammation [29][30][31]. Additionally, TTS patients have decreased concentrations of several amino acids, which are correlated in a proportionate way with LV systolic function [29,32].…”
Section: Emerging Concepts Of Takotsubo Syndrome Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced synthesis of Kreb's cycle intermediates and adenosine triphosphate results from an increase in myocardial glucose intake combined with a decrease in the available glycolysis metabolites, giving rise to a different metabolic profile in TTS than patients with AMI [28]. In a recent study, serum metabolic profile analysis showed that TTS is associated with a substantial rise in the plasmatic concentrations of ketone bodies, 2-hydroxybutyrate, and markers associated with fatty acid metabolism, which leads to endothelial dysfunction through the production of oxygen radicals and vascular inflammation [29][30][31]. Additionally, TTS patients have decreased concentrations of several amino acids, which are correlated in a proportionate way with LV systolic function [29,32].…”
Section: Emerging Concepts Of Takotsubo Syndrome Pathophysiologymentioning
confidence: 99%
“…In a recent study, serum metabolic profile analysis showed that TTS is associated with a substantial rise in the plasmatic concentrations of ketone bodies, 2-hydroxybutyrate, and markers associated with fatty acid metabolism, which leads to endothelial dysfunction through the production of oxygen radicals and vascular inflammation [29][30][31]. Additionally, TTS patients have decreased concentrations of several amino acids, which are correlated in a proportionate way with LV systolic function [29,32].…”
Section: Emerging Concepts Of Takotsubo Syndrome Pathophysiologymentioning
confidence: 99%
“…Our Special Issue presents innovative research [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and review [ 13 , 14 , 15 ] papers addressing many of these questions related to the fundamental OS involvement in the onset and progression of several acute and chronic diseases, and about the correlated biomarkers and potential therapies. Precisely, the 12 research articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] included in this Special Issue are focused on evidencing the OS role in diagnostics, signatures of the disease course, molecules involved, OS potential treatments and effects, and short- and long-term consequences.…”
mentioning
confidence: 99%
“…Our Special Issue presents innovative research [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and review [ 13 , 14 , 15 ] papers addressing many of these questions related to the fundamental OS involvement in the onset and progression of several acute and chronic diseases, and about the correlated biomarkers and potential therapies. Precisely, the 12 research articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] included in this Special Issue are focused on evidencing the OS role in diagnostics, signatures of the disease course, molecules involved, OS potential treatments and effects, and short- and long-term consequences. Precisely, Chen et al [ 1 ], by performing a nano-electrospray ionization–mass spectrometry (nanoESI-MS)-based lipidomic profiling study on lipid accumulation and oxidation in kidney cells in the chronic kidney disease (CKD) model, confirmed the key role of OS and lipid dysregulation in renal lipid droplet (LD) alteration at the molecular level.…”
mentioning
confidence: 99%
See 1 more Smart Citation